Raphael’s Religious Paintings and Their Early Restorations: Devotional Attention or Aesthetic Appreciation? - Cathleen Hoeniger (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This essay explores whether early restorers responded to the cult status of Raphael’s paintings, since Vasari records that several of his religious works carried spiritual power. Evidence from conservation research and from historical documents suggests that both aesthetic and devotional motivations were at play, but that the context in which the painting was housed, whether a religious institution or a private gallery, contributed significantly to the response.